Immunoactive preparations and regulatory responses in the respiratory tract: potential for clinical application in chronic inflammatory airway diseases. (2nd June 2020) - Feleszko, Wojciech; Rossi, Giovanni A.; Krenke, Rafal; Canonica, G. Walter; Van Gerven, Laura; Kalyuzhin, Oleg
ABSTRACT: Introduction: The prevalence of chronic inflammatory airway diseases is rising. Their treatment with corticosteroids increases infection risk, while overuse of antimicrobial agents may increase morbidity and antimicrobial resistance. Nonspecific immunomodulatory compounds alter immune responses to both infectious and atopic challenges. These compounds may offer an alternative approach for symptom reduction and prophylaxis against both infections and exacerbations in chronic inflammatory airway disease. Areas covered: We assessed the available data on the efficacy of nonspecific immunomodulators including bacterial lysates, synthetic compounds, and vaccines in chronic rhinosinusitis (CRS); allergic and non-allergic rhinitis; chronic obstructive pulmonary disease (COPD), and asthma. A search of PubMed was carried out using the 'Clinical Trials' filter for each condition and immunomodulatory product detailed below, where available, data from meta-analyses were reported. Expert opinion: Pre-clinical data has revealed a coherent mechanistic path of action for oral immunomodulators on the respiratory immune system, principally via the gut-lung immune axis. In patients with asthma, allergic rhinitis, CRS, and COPD immunomodulatory therapy reduces symptoms, exacerbations, hospitalizations, and drug consumption. However, data are heterogeneous, and study quality remains limited. A lack of high-quality recent trials remains the major unmet research need in the field.